1988
DOI: 10.1063/1.100126
|View full text |Cite
|
Sign up to set email alerts
|

Outdiffusion of oxygen and carbon in Czochralski silicon

Abstract: The outdiffusion behavior of oxygen and carbon in heat-treated Czochralski (CZ) silicon has been investigated by secondary ion mass spectroscopy. The results show that oxygen diffusion is greatly retarded by oxygen precipitation and strongly support a vacancy-dominant diffusion mechanism for oxygen in silicon. In carbon-doped CZ silicon, the diffusion of both oxygen and carbon is greatly enhanced at 750 °C, but is significantly retarded at 1000 °C. In conjunction with the infrared absorption data, the enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…It appears that oxygen and carbon also interact on an atomic level. It was observed that the out-diffusion of oxygen as well as of carbon is enhanced in the case of the presence of high concentrations of interstitial oxygen and substitutional carbon and leads to about the same enhanced diffusivity [40]. It is tempting to speculate that oxygen and carbon form either a molecular C i O i complex (corresponding to a CO molecule) or a corresponding CO 2 molecule which may be fast diffusing entities in silicon similar as suggested for O 2 in silicon [41].…”
Section: Oxygen Effectsmentioning
confidence: 88%
“…It appears that oxygen and carbon also interact on an atomic level. It was observed that the out-diffusion of oxygen as well as of carbon is enhanced in the case of the presence of high concentrations of interstitial oxygen and substitutional carbon and leads to about the same enhanced diffusivity [40]. It is tempting to speculate that oxygen and carbon form either a molecular C i O i complex (corresponding to a CO molecule) or a corresponding CO 2 molecule which may be fast diffusing entities in silicon similar as suggested for O 2 in silicon [41].…”
Section: Oxygen Effectsmentioning
confidence: 88%
“…8,25,37) Using Eq. (5), the diffusion distance at 1100°C for 3 h was 8.9 µm, that for 6 h was 13 µm, and that for 9 h was 15 µm.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that not only oxygen but also carbon is involved in the oxygen precipitation. 5,8,19,[23][24][25][26][27][28][29] It has also been reported that there is a clear correlation between carbon concentration and precipitate density, implying that carbon promotes oxygen precipitation. 5,6) Thermal donors are involved in oxygen precipitation and also in the supply of interstitial oxygen atoms to oxygen precipitation through formation and extinction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been suggested to interpret the phenomenon. Thus, the observed enhanced diffusion of oxygen in Si has been attributed to interactions of O i atoms with lattice vacancies [11,12], with self-interstitials [13], with metallic contaminants (for example copper, iron etc) [14] or non-metallic elements such as carbon [15], hydrogen [16], nitrogen [17] or isovalent dopants as Ge, Sn, Pb [18][19][20] or even with a second oxygen leading to fast diffusing oxygen dimers [21].…”
Section: Introductionmentioning
confidence: 99%